(untitled) (Bangladesh Journal of Agricultural Research, 2023)
Micronutrient deficiency, especially zinc and boron deficiency, commonly occurs in Bangladesh soils. Nevertheless, common diets of this country’s people are often deficient in zinc. Thus, application of zinc and boron has significant value in enhancing crop yield as well as zinc and boron content in crop. With this understanding, field experiments were conducted in two consecutive seasons of 2018-19 and 2019-20 at Bangladesh Agricultural Research Institute (BARI) farm, Gazipur under the agroecological zone 28 (Madhupur Tract). Texturally the soil was sandy clay loam with 6.2 pH, 1.26% organic matter, 0.99 mg kg-1 zinc and 0.13 mg kg-1 boron content. Treatments consisted of a factorial arrangement of three levels of zinc (0, 2, 4 kg ha-1) and three levels of boron (0, 1, 2 kg ha-1) in a randomized complete block design (RCBD) with three replications. Combined application of Zn and B significantly increased the foliage and seed yield as well as their (zinc and boron) contents. On an average, among the treatment combinations, Zn4B1 produced the highest foliage yield (4.55 t ha-1) and Zn2B2 gave the highest seed yield (1.99t ha-1). The highest zinc and boron contents were found in Zn4B2 treatment for both foliage and seeds. Agronomic biofortification of zinc in coriander could be possible without reducing yield through the use of Zn4B1 treatment for foliage purpose and Zn2B2 for seed purpose. Bangladesh J. Agril. Res. 47(1): 91-98, March 2022